Midwife-performed checklist and ultrasound to identify obstetric conditions at labour triage in Uganda: A quasi-experimental study. (May 2021) - Mulowooza, Jude; Santos, Nicole; Isabirye, Nathan; Inhensiko, Innocent; Sloan, Nancy L.; Shah, Sachita; Butrick, Elizabeth; Waiswa, Peter; Walker, Dilys
Abstract: Objective: The aim of this study was to evaluate the effect of a midwife-performed checklist and limited obstetric ultrasound on sensitivity and positive predictive value for a composite outcome comprising multiple gestation, placenta praevia, oligohydramnios, preterm birth, malpresentation, abnormal foetal heart rate. Design: Quasi-experimental pre-post intervention study. Setting: Maternity unit at a district hospital in Eastern Uganda. Interventions: Interventions were implemented in a phased approach: standardised labour triage documentation (Phase 1), a triage checklist (Phase 2), and checklist plus limited obstetric ultrasound (Phase 3). Participants: Consenting women presenting to labour triage for admission after 28 weeks of gestation between February 2018 and June 2019 were eligible. Women not in labour or those requiring immediate care were excluded. 3, 865 women and 3, 937 newborns with similar sample sizes per phase were included in the analysis. Measurement and findings: Outcome data after birth were used to determine true presence of a complication, while intake and checklist data were used to inform diagnosis before birth. Compared to Phase 1, Phase 2 and 3 interventions improved sensitivity (Phase 1: 47%, Phase 2: 68.8%, Phase 3: 73.5%; p ≤ 0.001) and reduced positive predictive value (65.9%, 55%, 48.7%, p ≤ 0.001) for the composite outcome. No phase differences in adverse maternal or foetal outcomes were observed. Conclusion: Both a triage checklist and a checklist plus limited obstetric ultrasound improved accurate identification of cases with some increase in false positive diagnosis. These interventions may be beneficial in a resource-limited maternity triage setting to improve midwives' diagnoses and clinical decision-making.